2020
DOI: 10.1371/journal.pone.0234157
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antioxidant potential, in vivo toxicity, and polyphenolic composition of Eugenia selloi B.D.Jacks. (pitangatuba), a Brazilian native fruit

Abstract: Brazilian native fruits are a rich source of polyphenolic compounds that can act as antiinflammatory and antioxidant agents. Here, we determined the polyphenolic composition, anti-inflammatory mechanism of action, antioxidant activity and systemic toxicity in Galleria mellonella larvae of Eugenia selloi B.D.Jacks. (synonym Eugenia neonitida Sobral) extract (Ese) and its polyphenol-rich fraction (F3) obtained through bioassay-guided fractionation. Phenolic compounds present in Ese and F3 were identified by LC-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…The S8 subfraction is obtained through chemical fractionation of Eugenia selloi pulp extract. The chemical composition of the pulp extract and its fraction is published elsewhere ( Lazarini et al, 2020 ). Bioactive fraction named F3 was submitted to subfractionation for chemical and biological refinement purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The S8 subfraction is obtained through chemical fractionation of Eugenia selloi pulp extract. The chemical composition of the pulp extract and its fraction is published elsewhere ( Lazarini et al, 2020 ). Bioactive fraction named F3 was submitted to subfractionation for chemical and biological refinement purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The acute toxicity of the EEP was determined in a G. mellonella L. model to provide preliminary evidence on the potentially toxic effects of the extract [67] . The larvae were maintained at 37 °C in a BOD incubator until use.…”
Section: Methodsmentioning
confidence: 99%
“…The acute toxicity of the EEP was determined in a G. mellonella L. model to provide preliminary evidence on the potentially toxic effects of the extract. [67] The larvae were maintained at 37 °C in a BOD incubator until use. Larvae with no signs of melanization, weighing 200 to 300 mg, were randomly selected for each group (n = 8).…”
Section: Acute Toxicity System In Vivo Using Galleria Mellonella Modelmentioning
confidence: 99%
“…Lazarini et al (2020) showed that oral treatment with ethanolic extract of E. selloi fruits promoted a decrease in neutrophils by 58% and 70% at concentrations of 3 and 10 mg/kg, respectively. A methanolic extract of E. uni ora leaves (100 mg/kg) reduced the number of leukocytes to 4.84 ± 1.97 x 106 mL compared to untreated animals (10.04 ± 2.64 × 106 mL)(Sobeh et al 2019).…”
mentioning
confidence: 99%